The Influence Of The Discovery Learning Model Assisted With Power Point Media On Students' Activities And Learning Outcomes On The Subject Of Colloids - Yolanda, Firsil Liya; Juwitaningsih, Tita (Universitas Lampung, 2024)
The Influence Of The Discovery Learning Model Assisted With Power Point Media On Students' Activities And Learning Outcomes On The Subject Of Colloids. This research aims to determine the influence of learning outcomes and student activities. The population and sample in this study were two classes of class XI high school students in the city of Medan, namely class XI4 as the experimental class and XI1 as the control class. The data taken in this research are test instruments in objective form and scores on student learning activity observation sheets. The research results show that there is a difference between the experimental class taught using the Discovery Learning model assisted by Power Point media compared to the control class which only uses conventional methods. This can be proven from the posttest average score for experimental class learning outcomes which is higher than the control class. Likewise, the learning activity of the experimental class was higher than that of the control class. From the results of the posttest hypothesis test using the t-test, it was found that tcount>ttable = 5,457 > 2.04. The results of students' learning activities in the experimental class obtained an average of 75.3 and the control class 52.7. It can be concluded that there is an influence of the Discovery Learning learning model assisted by Power Point media on students' activities and learning outcomes on the subject of colloids.Keywords: Learning Outcomes, Activities, Discovery Learning, Power PointDOI: 10.23960/jppk.v13i2.29716